1973
DOI: 10.1111/j.1550-7408.1973.tb00921.x
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive Transfer of Immunity to Plasmodium berghei by Spleen and Lymph Node Cells from Young and Old Mice*

Abstract: SYNOPSIS. Different numbers of spleen and lymph node cells of 6‐week and 6–8 month A/J mice, immune to Plasmodium berghei, were transferred into normal 4‐week old mice. Better protection was observed with 2.5 × 10s than with 107 spleen cells, and spleen cells afforded better protection than an equal number of lymph node cells. Further, spleen cells from older mice were more effective than those from young animals. Possible mechanisms of immunity transfer are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1975
1975
1998
1998

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Singer et al (1955) concluded that young rats are unable to produce a protective immune response quick enough to prevent an acute infection with high mortality (Table 1, B(ii)). Kasper & Alger (1973) transferred spleen cells from old mice and 6-week-old mice, both groups immune to P. berghei, into young recipients. When the latter were challenged the cells of old mice were found to be more effective at transferring protection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Singer et al (1955) concluded that young rats are unable to produce a protective immune response quick enough to prevent an acute infection with high mortality (Table 1, B(ii)). Kasper & Alger (1973) transferred spleen cells from old mice and 6-week-old mice, both groups immune to P. berghei, into young recipients. When the latter were challenged the cells of old mice were found to be more effective at transferring protection.…”
Section: Discussionmentioning
confidence: 99%
“…berghei in the rat is not clear. Subtle changes in erythropoiesis have been cited (Zuckerman, 1957) whilst other workers consider that young rats die because of an inadequate immune response (Singer, Hadfield & Lakonen, 1955;Spira, Silverman & Gaines, 1970;Kasper & Alger, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…Alger et al (1972) demonstrated age-dependent protective immunity against P. berghei in inbred A/J mice, and Kasper and Alger (1973) adoptively transferred this imm unity from old to young mice using splenic T cells. Like untreated controls, naive, 4-week-old mice receiving cells from naive, 6± 8-month-old retired breeders died within 30 days of challenge, each with a fulminant parasitaemia.…”
Section: Age-dependent Immune Function Inmentioning
confidence: 99%